Alterations of the Human Skin N- and O-Glycome in Basal Cell Carcinoma and Squamous Cell Carcinoma - Möginger, Uwe; Grunewald, Sonja; Hennig, René; Kuo, Chu-Wei; Schirmeister, Falko; Voth, Harald; Rapp, Erdmann; Khoo, Kay-Hooi; Seeberger, Peter H.; Simon, Jan C.; Kolarich, Daniel (Frontiers in Oncology, 2018)
The glycome of one of the largest and most exposed human organs, the skin, as well as glycan changes associated to non-melanoma skin cancers have not been studied in detail to date. Skin cancers such as basal cell carcinoma and squamous cell carcinoma are among the most frequent types of cancers with rising incidence rates in the ageing population. We investigated the healthy human skin N- and O-glycome and its changes associated to BCC and SCC. Matched patient samples were obtained from frozen biopsy and formalin-fixed paraffin-embedded tissue samples for glycomics analyses using two complementary glycomics approaches: porous graphitized carbon nano liquid chromatography electro spray ionization tandem mass spectrometry and capillary gel electrophoresis with laser induced fluorescence detection. The human skin N-glycome is dominated by complex type N-glycans that exhibit almost similar levels of α2-3 and α2-6 sialylation. Fucose is attached almost exclusively to the N-glycan core. Core 1 and core 2 type O-glycans carried up to three sialic acid residues. An increase of oligomannose type N-glycans and core 2 type O-glycans was observed in BCC and SCC, while α2-3 sialylation levels were decreased in SCC but not in BCC. Furthermore, glycopeptide analyses provided insights into the glycoprotein candidates possibly associated with the observed N-glycan changes, with glycoproteins associated to binding events being the most frequently identified class.